Formulation of Tembelekan Leaf Hand Sanitizer (Lantana camara L.) and Antibacterial Activity Test Against Escherichia coli and Staphylococcus aureus - Fauzi, Ziza Putri Aisyia; Putri, Cut Intan Annisa; Aska, Nawalul; Utami, Dinda Sari (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Disease-causing microorganisms stick to hands every day through physical contact with the environment. One of the easiest and most appropriate ways to clean them is to wash hands with soap and clean water. This study aims to determine the formulation of tembelekan leaf hand sanitizer (Lantana camara L.) and test its antibacterial activity against Escherichia coli and Staphylococcus aureus. Assessment of the arrangements acquired incorporates organoleptic tests with libertine tests, homogeneity, pH, spreadability, dependability, bothering to chip in skin, and antibacterial movement against Staphylococcus aureus and Escherichia coli by agar dispersion utilizing poke holes. The outcomes showed that the hand sanitizer readiness containing 10% tembelekan leaf remove was the best planning since it was liked by specialists, stable when put away at room temperature for a very long time, didn't cause bothering, and had solid antibacterial movement so that the tembelekan leaf gel planning utilized as a characteristic natural substance can be utilized to clean hands from microscopic organisms that is simple, reasonable and protected to use without utilizing water.